Wear resistance and lubricity of the spiral oil distribution profile of the valve guide sleeves of an internal combustion engine - O.V. Dykha; A.A. Vychavka; M.O. Dykha (Проблеми трибології)
Valve guides are crucial for maintaining the correct alignment, positioning, and clearance of the valve stem as it moves in the cylinder head. When the guides are heavily worn, the engine begins to consume oil and the valve mechanism becomes noisy. Reliable lubrication of the inner surface of the guide bushing ensures the wear resistance of the valve-guide pair. This work proposes a special tool and technology for obtaining an oil-retaining profile on the inner surface of the valve guide, which increases the oil capacity of the surface, and therefore improves the lubrication conditions in the valve-guide friction pair. A gas labyrinth seal is created in the connection, which prevents oil from entering the combustion chamber. The surface of the bushing bore is strengthened due to the sealing of the surface. The results of wear tests of guide bushings with spiral oil-retaining grooves confirmed their effectiveness in terms of wear resistance. The wear rate of the bushings with grooves for the entire time range of the tests is on average 20% less than the wear rate of the bushings without grooves